Promotion Analysis and Information Systems on Service Quality and Implications on Work Productivity - Evan Nugraha; Rini Mulyani Sari; Arif Yunan (Technium Social Sciences Journal, 2020)
The impact of advancement and data frameworks in supporting the improvement of an organization association will positively bring benefits. In the advancement of an organization, data frameworks will be aided request to improve the presentation of the organization. With superior it will have the option to keep up hierarchical responsibility. A solid responsibility will influence the administration nature of the organization. Administration quality is an extremely key issue for expanding consumer loyalty. The ramifications of administration quality will build the work profitability of the organization. From this wonder, research is completed utilizing special factors, data frameworks, administration quality and work efficiency with the object of exploration in an organization. This examination utilizes a quantitative methodology with informative exploration techniques. From the examination results, it is discovered that advancement (X1) and data frameworks (X2), administration quality (Y) and work efficiency (Z) have a huge impact.